Integrated Approach In Developing Reflective Competence Of Future Primary Class Teachers - A.I.Khayitov (Euro Asian Journal Publishing, 2024)
The article talks about an integrative approach to the development of reflexive competence in future primary school teachers
Keywords: primary school teacher; integration; integrative approach